A map of the topsoil organic carbon content of Europe generated by a generalized additive model. (16th October 2014) - de Brogniez, D.; Ballabio, C.; Stevens, A.; Jones, R. J. A.; Montanarella, L.; van Wesemael, B.
Summary There is an increasing demand for up‐to‐date soil organic carbon (OC) data for global environmental and climatic modelling. The aim of this study was to create a map of topsoil OC content at the European scale by applying digital soil mapping techniques to the first European harmonized geo‐referenced topsoil (0–20 cm) database, which arises from the Land use/Cover Area frame statistical Survey (LUCAS). A map of the associated uncertainty was also produced to support careful use of the predicted OC contents. A generalized additive model (GAM) was fitted on 85% of the dataset (R2 = 0.29), using OC content as dependent variable; a backward stepwise approach selected slope, land cover, temperature, net primary productivity, latitude and longitude as suitable covariates. The validation of the model (performed on 15% of the data‐set) gave an overall R2 of 0.27 and an R2 of 0.21 for mineral soils and 0.06 for organic soils. Organic C content in most organic soils was under‐predicted, probably because of the imposed unimodal distribution of our model, whose mean is tilted towards the prevalent mineral soils. This was also confirmed by the poor prediction in Scandinavia (where organic soils are more frequent), which gave an R2 of 0.09, whilst the prediction performance (R2) in non‐Scandinavian countries was 0.28. The map of predicted OC content had the smallest values in Mediterranean countries and in croplands across Europe, whereas largest OC contents were predicted in wetlands, woodlands and mountainous areas. The map of the predictions' standard error had large uncertainty in northern latitudes, wetlands, moors and heathlands, whereas small uncertainty was mostly found in croplands. The map produced gives the most updated general picture of topsoil OC content at the European Union scale.